Caracterización socioeconómica de las microcuencas de los cantones Puyango y Pindal de la cuenca hidrográfica Puyango. - Cartuche Cango, Tania Denisse (2025)
Understanding the socioeconomic dynamics of micro-watersheds is crucial for sustainable water resource management and fostering the holistic development of local communities. This study examines the hydrographic units of Cochurco, Chirimoyo, and Pavas, located in the Puyango and Pindal cantons, which form part of the Puyango River Basin. Data were gathered through field visits, interviews, qualitative analysis, and the use of geospatial tools such as ArcGIS and QGIS to produce thematic maps and insights on demographics and economic activities. The findings highlight a varied vegetative cover and agricultural soils, with maize as the predominant crop. However, limited irrigation infrastructure and poor water quality restrict access to water resources, affecting both domestic use and agricultural productivity. Seasonal droughts further exacerbate water scarcity, particularly in the Cochurco hydrographic unit, which has the largest population and land area. The study also revealed inefficient water resource management, marked by the absence of irrigation boards, which deepens inequities in water distribution. These challenges emphasize the need for integrated strategies that include infrastructure upgrades, organizational capacity building, and sustainable practices to ensure equitable water access and improve community livelihoods. This analysis provides essential insights for planning and managing water resources in the micro-watersheds of Puyango and Pindal.